Unlock the potential of vaccines in food-producing animals - Laxminarayan, R.; Gleason, A.; Sheen, J.; Saad-Roy, C.M.; Metcalf, C.J.; Palmer, G.H.; Fèvre, Eric M. (American Association for the Advancement of Science, 2024)
Animal vaccines help maintain healthy livestock and poultry populations, improve food safety, and reduce the transmission of zoonotic disease to humans (1). Such vaccines can reduce the clinical impact of pathogens on an individual animal, an important ethical consideration for improving animal welfare. However, the extent of routine vaccination among food-producing animals in low- and middle-income countries (LMICs) is low and considerably lags vaccination rates in high-income countries (HICs) (see fig. S1). Many of the existing gaps in the area of vaccine development and deployment for terrestrial food-producing animals could be hugely aided by changes in policy and increases in funding. But this is also a scientific problem of fundamental importance and applied relevance. Improvement could simultaneously help mitigate climate change and pandemic risk, tackle antimicrobial resistance, and fight poverty. Few global investments could claim to have similarly broad benefits at so modest a cost.